Pengaruh Model Project Based Learning Tema 2 Terhadap Hasil Belajar Siswa Kelas IV UPTD SDN Klampis Timur Bangkalan - Ajeng Putri Dewi; Conny Dian Sumadi (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this study was to determine the significant effect of applying the project based learning model on the learning outcomes of grade IV Elementari School of Klampis Timur. This research is a quantitative research with the method used is quasi-experimental and the design used is the nonequivalent pretest-posttest control group design. The population consisted of 30 students from class IV SDN Klampis Timur. Sampling used non-probability sampling, namely the sample used was 15 control groups and 15 experimental groups. This study used an experimental group and a control group. Based on the results of data analysis using the Mann-Whitney test with a significance level of 0.05, the Asymp sig.(2-tailed) result is 0.000 <0.05 and the Z score is -3.734, so Ho is rejected and H1 is accepted, so it can be concluded that there is an influence between the experimental group and the control group, the treatment given had a significant effect on the project based learning method on the learning outcomes of class IV Elementary School Theme 2 students.